2007
DOI: 10.1055/s-2006-952012
|View full text |Cite
|
Sign up to set email alerts
|

Kann Lebensqualität bei Demenzkranken valide bestimmt werden?

Abstract: QoL-instruments, applicable to all stages of dementia should be preferred, because longitudinal QoL-measures are more meaningful than cross sectional analyses. The patients' perspective should be taken into consideration as long as possible, since proxies assess the QoL of dementia patients differently from the persons affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…Proxies might rate patients’ quality of life differently than patients themselves, if they were capable to do so (weak inter-rater reliability) [ 28 ]. The development of QoL-instruments for all severity levels in a self-assessed manner or at least of more reliable proxy-person-instruments [ 28 ] is still needed [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proxies might rate patients’ quality of life differently than patients themselves, if they were capable to do so (weak inter-rater reliability) [ 28 ]. The development of QoL-instruments for all severity levels in a self-assessed manner or at least of more reliable proxy-person-instruments [ 28 ] is still needed [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging the problem of potential bias of proxy reports, we chose a proxy rating for QoL in the THERAD study, for several reasons. Firstly, it has been demonstrated with increasing severity of the disease that patient ratings must mostly be replaced by proxy ratings [ 55 ],[ 56 ], even if Logsdon and colleagues showed in 2002 that patients can rate their own QoL until the late stages [ 28 ]. This last study showed that the correlation between caregiver’s rating and patient’s rating was greatest for subjects in the middle tertile of cognitive function, and the recruitment of our centre for the THERAD study is mainly moderately affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Schließlich stellt die Erfassung der Lebensqualität bei Demenz auch vor erhebliche methodische Herausforderungen [10]. Die Zuverlässigkeit subjektiver Selbstauskünfte kann auf-grund kognitiver Beeinträchtigungen und verminderter Krankheitseinsicht kompromittiert sein [11].…”
Section: Die Lebensqualität Von Menschen Mit Demenzunclassified